Bees Poison And His Joint In Diseases Effect - Makhamadkhodjayeva.MA (Genius Journals, 2025)
This article joint diseases in treatment bees healing of poison ( apitoxin ). effect him to the joints and to the organism effect effect will be lit. Bees by calling treatment the main type of treatment methods advantages is displayed .
Keywords: apitoxin polypeptides; mellitin; apamin